Pandemics and travel : COVID-19 impacts in the tourism industry - Seabra, Cláudia; Paiva, Odete; Silva, Carla; Abrantes, José Luís (Tourism security-safety and post conflict destinations., 2021)
Tourism is not only affected by pandemics and epidemics but also contributes to their spread, affecting not only tourists but also the communities in their destinations. The COVID-19 pandemic brought about a new crisis, challenging the travel industry more than ever before. Several studies have suggested that there will be long-term severe effects that could continue for an unspecified period of time across the world, both medically, socially and economically. Pandemics and Travel: COVID-19 Impacts in the Tourism Industry analyses the wider impacts of epidemics, diseases and virus outbreaks on tourism and mobility. Chapters examine a wide range of interrelated issues, including the concept of Health Risk and Tourism, the impacts of the recent COVID-19 crisis on tourism activity in several countries, and considers new challenges that the tourism industry will face in the post-COVID era. This book is essential reading for researchers seeking to understand the ongoing effects of pandemics on travel, tourism, hospitality and health industries.